2018
DOI: 10.1038/s41375-018-0180-3
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression profile of leukemic stem cell markers for combinatorial targeted therapy in AML

Abstract: Targeted immunotherapy in acute myeloid leukemia (AML) is challenged by the lack of AML-specific target antigens and clonal heterogeneity, leading to unwanted on-target off-leukemia toxicity and risk of relapse from minor clones. We hypothesize that combinatorial targeting of AML cells can enhance therapeutic efficacy without increasing toxicity. To identify target antigen combinations specific for AML and leukemic stem cells, we generated a detailed protein expression profile based on flow cytometry of primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
232
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(276 citation statements)
references
References 55 publications
8
232
1
1
Order By: Relevance
“…Interestingly, CD9 antigen level of expression is identical between LSCs and AML blast cells and is not expressed on normal HSCs. These findings are particularly relevant as the majority of antigens associated with LSCs (ie, TIM3, CLL1, and CD244) are less expressed on these cells compared to bulk cells and are frequently coexpressed on normal HSCs and progenitors . Recently, Coustan‐Smith et al published a study on MRD monitoring in AML by MFC and, interestingly, they found an overexpression of CD9 on blast cells (in 30% of AML cases) compared to physiologic myeloblasts .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, CD9 antigen level of expression is identical between LSCs and AML blast cells and is not expressed on normal HSCs. These findings are particularly relevant as the majority of antigens associated with LSCs (ie, TIM3, CLL1, and CD244) are less expressed on these cells compared to bulk cells and are frequently coexpressed on normal HSCs and progenitors . Recently, Coustan‐Smith et al published a study on MRD monitoring in AML by MFC and, interestingly, they found an overexpression of CD9 on blast cells (in 30% of AML cases) compared to physiologic myeloblasts .…”
Section: Discussionmentioning
confidence: 99%
“…38 Moreover, antigen targeting is an appealing approach in cancer treatment. 29,39 Routinely, leukapheresis products are evaluated by FCM to enumerate CD34 1 cells, and simultaneous evaluation of aberrant CD7 expression on CD38 1 CD34cells would be feasible in most laboratories as performed in diagnostic and MRD settings of AML and MDS, as shown by Zeijlemaker et al 28 Targeted NGS offers the advantage of accurate prediction of which specific mutations confer an actual risk of tMN, albeit this perspective will be consolidated in the future. The accumulating evidence pointing to the increased risk of tMN in patients with CH who are treated with ASCT makes close monitoring with early intervention an alluring and feasible option.…”
Section: Discussionmentioning
confidence: 99%
“…Both CD44 and GPR56 were expressed on >90% of CD34 + 38 − HSPCs, while the markers CD117, CD305, CD47 and CD33 were prevalent in substantial numbers of normal HSPCs with a surface expression on 50%-90% of cells, comparably to what has been reported. [21][22][23][24][25][26][27][28] The remaining markers were hardly expressed on CD34 + 38 − HSPCs ( Figure 1B).…”
Section: Mfc Analysis Of Cell Surface Markers For Residual Leukemicmentioning
confidence: 99%
“…Since no single marker showed an ideal expression profile for leukemic cell enrichment, we aimed to determine the best marker combination enabling enrichment of residual leukemic cells in a maximum number of AML cases. Although CD47, GPR56, CD33, CD305 and CD45RA were expressed on >90% blasts of the majority of AML cases evaluated, these markers were not considered further for enrichment, because they were also widely expressed on normal hematopoietic cell subtypes including CD34 + 38 − HSPCs [21][22][23][24][25] ( Figure 1B and Figure S2). From that perspective CLL-1, TIM-3, CD117 and CD123 were the most promising markers, since they were only expressed on either a distinct progenitor population or on small subtypes of mature leukocytes.…”
Section: Mfc Analysis Of Cell Surface Markers For Residual Leukemicmentioning
confidence: 99%